Synthesis, characterization and catalytic activity of palladium(ii)-1,3-bis(phenylmethyl) benzimidazolium bromide in heck reaction / Mohamad Azamuddin Mustakim - Mustakim, Mohamad Azamuddin (Faculty of Applied Sciences, 2017)
Palladium is used as a catalyst for carbon-carbon coupling such as in Heck, Stille and Suzuki reaction. This research reports on a palladium catalyst for Heck reaction namely palladium(II)-1-3-bis(phenylmethyl) benzimidazolium bromide. The Nheterocyclic carbene (NHC) ligand was prepared by reacting benzyl bromide with benzimidazole while the palladium catalyst was prepared by reacting palladium chloride with the synthesized NHC ligand. The palladium catalyst has been successfully synthesized and characterized by using Fourier transform infrared (FTIR), 1 H and 13C nuclear magnetic resonance (NMR), UV-Vis spectroscopy and CHNS elemental analysis. FTIR spectra confirm the present of important group in the synthesized complex such as C=N group. NMR and CHNS elemental analysis results also supported in the confirmation of the complex structure. UV -Vis spectroscopy results showed the absorption maxima of Pd2 + cation and NHC ligand. The blue shifting in UV-Vis spectra for palladium catalyst give an evidence of the successfulness of the complexation. The preliminary complexation between Pd2+ cation and N-heterocyclic carbene (NHC) ligand shows stoichiometric of 1 Pd2+ cation to 2 NHC ligand. The catalytic activity of the palladium catalyst was studied on Heck carbon-carbon coupling reaction between l-bromo-4-nitrobenzene and styrene. Two parameters of the reaction were studied which are different catalyst loading and effect of different reaction time. The results show that excellent catalytic activity is achieved using catalyst loading of 0.5 mmol % and 60 minutes of reaction time.